Jurnal Budaya Aisatsu dan Ojigi (Studi Fenomenologi Budaya Komunikasi Pada Pekerja Hotel Kyuukamura Kishu Kada) - Yusuf, Reinaldy; Lusiana, Yusida; Widodo, Heri (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2021)
The purpose of the study was to find out about the communication culture of Japanese society, namely verbal Aisatsu and non-verbal Ojigi communication practiced by hotel workers Kyuukamura Kishu Kada using phenomenology studies. This research is a qualitative descriptive study using interview techniques as a data collection technique. There are 5 informants from this research. The results found in this study are the Aisatsu verbal communication culture practiced by Kyuukamura Kishu Kada workers varies depending on the interlocutor and the situation. For non-verbal culture, Ojigi is done to show apologies, thanks, and respect for the other person. The more bent in doing Ojigi, the feelings shown are getting deeper. Employees at Kyuukamura Kishu Kada also realize that Aisatsu and Ojigi are very important Japanese communication culture and play an important role, especially in Kyuukamura Kishu Kada.